Some Surprising Series Sums. Issue 1 (1st January 2023) - Gordon, Russell A.
Summary: We establish the convergence of a family of series for which the usual convergence tests fail. In addition, we show how to use elementary methods to find the sums of the series. A wealth of problems for both calculus students and real analysis students can be obtained from this collection of series and connections can be made to both differential equations and hypergeometric functions.